PENIPUAN SHORT MESSAGE SERVICE (SMS) TERHADAP KONSUMEN PROVIDER TELEPON SELULER DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - NOVANEMA DUHA; T KEIZEIRINA DEVI AZWAR; WINDHA WINDHA (TRANSPARENCY, 2013)
Technological advances especially in the telecommunications sector is growing very rapidly. Product/communication tool created one of which is a cell phone/mobile phone. The development of this technology didnot rule out the occurrence of fraudulent short message service (SMS) via mobile phoneto consumers. Attendance Law No.8 of 1999 on Consumer Protection as protect the consumer in thefrom of fraud via SMS.The nethid if research used in writing this thesis is normative legal research methods, by collecting data from multiple reference either through books, legislation, website, and other reference sources.Based on the survey results revealed that consumers’ rights cellular provider refers to Law No.8 of 1999 on Consumer Protection. While the information and personal data not specifically, but partially regulated in Law No.36 of 1999 on Telecommunication and Law No.11 of 2008 on Information and Electronic Transactions. Further legal safeguards for consumers on mobile phone provider fraud committed via SMS, can be a preventive law efforts and the efforts of repressive laws, and to do preventive measures for the occurence of fraud via SMS